Home automated lighting control using atmel AVR microcontroller - Leong, Ching Hoong (Universiti Malaysia Sarawak, UNIMAS, 2006)
The Home Automation Lighting Control System is a system that automatically switches on/off the light through sensors. This system allows user to save their time and money. When the users go out from the house, they need not to worry about switching off the light manually. This is because the Passive Infrared Motion (PIR) sensors in the house will help to do so. During the day time, the Light Sensor which is placed outdoor will help to control the Passive Infrared Motion sensor in the house. In this case, after the user enters the house, the light will not be switched on during day time but it will be switch on at night instead. The Home Automation Lighting Control System can be further extended to become a more complete system by adding additional Home Security features in the future.